Raising the flag of vigilance on Mpox outbreak in Indonesia: are we prepared? - Adnyana, I Made Dwi Mertha; Maulana, Sidik; Lutfian, Lutfian; Adiwinoto, Ronald Pratama (Svāsthya: Trends in General Medicine and Public Health, 2024)
In the wake of the COVID-19 pandemic, the world has become acutely aware of the devastating impact of infectious diseases on public health, economies, and societies. As we gradually recover from the aftermath of COVID-19, another potential threat looms on the horizon, mpox, formerly known as monkeypox. The recent surge in mpox cases worldwide has prompted health authorities to sound an alarm, and Indonesia, as a populous nation with a complex healthcare system, must ask itself: Are we prepared for this emerging challenge?. The question "Are we prepared?" may not have a simple yes or no answer. Instead, it should serve as a reminder of the need for vigilance, adaptation, and continuous improvement in public health systems. As we navigate this new health challenge, the true measure of Indonesia's preparedness is its ability to respond swiftly, effectively, and equitably to protect the health and well-being of all citizens.